Development of a verbal and non-verbal communication model between learning companion humanoids and the elderly / Nor Ayu Meor Ahmad - Nor Ayu , Meor Ahmad (2018)
As the number of elderly people in Malaysia increases, they might feel lonely as caregivers struggle to give care and provide companionship to the elders. Loneliness can lead to mental diseases like depression and dementia that can have a negative impact on the quality of life of both elderly people and their caregivers. Therefore, a solution to overcome this problem is by using humanoids as companions for the elders and to encourage them to gain knowledge at a later age. This study aimed to develop a model on verbal and non-verbal communication between learning companion humanoids and elderly humans who live alone. Design and Development Research Approach (DDR) was adopted which consists of three phases. Phase 1 is the needs analysis phase that utilized survey questionnaires on 100 respondents and interviews on 5 participants to investigate the need to develop a communication model between humanoids and the elderly. The data was analyzed through Statistical Package for the Social Sciences (SPSS) and interpreted based on the values of mean and standard deviation. In Phase 2, Nominal Group Technique (NGT) and Interpretive Structural Modeling (ISM) were used in developing the model with aid from 8 heterogeneous experts. Data for this phase was interpreted based on the communication model generated by the ISM software and the classifications and relationships of the elements. The final phase adopted a modified Fuzzy Delphi Method (FDM) to evaluate the developed model in its suitability to facilitate successful communication between learning companion humanoids and elders who live alone. 15 experts shared their views by responding to a seven-point linguistic scale survey questionnaire. Experts’ consensus for all the questionnaire items were determined by the calculation of the threshold values (d) whereas the defuzzification values (Amax) indicated the agreement of the experts. The findings from Phase 1 showed that there was a need to develop a communication model for humanoids and elders who live on their own. Results of Phase 2 constitute the development of the model which comprises of 32 elements determined through experts’ views. In the reviewing of the communication model, the experts had divided the elements into four domains and four clusters to interpret and understand the roles of the elements better. Finally, the results of Phase 3 showed that all the items have met the requirements of the triangular fuzzy number and defuzzification process which indicated that all the experts consensually agreed with the questionnaire items. The model is expected to act as a guideline in facilitating successful communication between learning companion humanoids and elders who live alone. Therefore, the results of the study can benefit the fields of education, health and robotics at the same time and improve the quality of life of elders who live alone.